Un método sencillo para priorizar la conservación de los bosques nubosos de Guatemala, usando Passalidae (Coleoptera) como organismos indicadores - Schuster, Jack C.; Cano, Enio B.; Cardona, Catherine (Instituto de Ecología, A.C., 2000)
Passalidae, for various reasons, are good indicators of endemism. We found 66 species of Passalidae in 32 cloud forests in Guatemala. In order to prioritize conservation of these forests, we established a method that evaluated passalid species richness, endemism and similarity among guilds, and forest conservation state. Thus, we suggest seven sites of very high priority and five of high priority for protection in Guatemala. This prioritization method, although not evaluating all ideal parameters, works as a rapid and cheap evaluation method for making urgent decisions concerning the protection of montane wet (cloud) forests.